Customers' Preferences Toward Shariah Compliant Services in Banks Among Academicians and Non-Academicians in Higher Education Institutions (HEIs) in Pahang - Abbas, R.; Abd Kadir, M. R. (Universiti Sains Islam Malaysia, 2024)
The purpose of this paper is to examine the main factors that influence customers to deal with Shariah compliant services particularly in a dual banking environment in Pahang. This study presents primary data collected by self-administered questionnaires involving a sample of 240 academician and non-academicians in Higher Education Institutions (HEIs) in Pahang. The study was set out to establish a ranking of the various factors which influence their bank selection decision and seek to determine homogeneous academician and nonacademician are in relation to their Shariah service selection decision. The factors are analyzed using t-test. This study revealed that the selection of Shariah compliant services appeared to be predominantly a combination between quality services and the lowest service charges by banks. More significant differences in preferences were found when academicians were compared with non-academicians in the Shariah service selection decision.